MILK PRICE PREDICTING WITH HOLT WINTERS AND ORDINARY LEAST SQUARES - Filiz BASAGAOGLU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
In this research, smoothing methods and the Ordinary Least Squares (OLS) method for predicting producer milk prices in Turkey is implemented. Holt-Winters multiplicative (HWM) method and Holt-Winters additive (HWA) method are included in the exponential smoothing methods. Producer milk prices data belong to January 1st, 2010 to December 31st, 2019 period and gathered from the Turkish Statistical Institute. According to the given results, OLS method is fitted the data and has good root mean square error (RMSE) and determination coefficients (R2).